The Impact Of Knowledge Management Implementation On Operational Efficiency And Profitability: A Study On Meteor Learning Sdn Bhd (MLSB) - Narayanan, Kalpana (2006)
The researcher proposes to conduct a case study on the impact of knowledge management implementation on operational efficiency and profitability of Meteor learning Sdn Bhd (MLSB), as well as to recommend an appropriate knowledge management system for MLSB to support its knowledge management initiatives.